2014
DOI: 10.1063/1.4891982
|View full text |Cite
|
Sign up to set email alerts
|

Device modeling of perovskite solar cells based on structural similarity with thin film inorganic semiconductor solar cells

Abstract: Device modeling of CH3NH3PbI3−xCl3 perovskite-based solar cells was performed. The perovskite solar cells employ a similar structure with inorganic semiconductor solar cells, such as Cu(In,Ga)Se2, and the exciton in the perovskite is Wannier-type. We, therefore, applied one-dimensional device simulator widely used in the Cu(In,Ga)Se2 solar cells. A high open-circuit voltage of 1.0 V reported experimentally was successfully reproduced in the simulation, and also other solar cell parameters well consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
181
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(185 citation statements)
references
References 30 publications
4
181
0
Order By: Relevance
“…This was attributed to the crystal defects. It was assumed that the rotation of the PI3 octet may have been restricted to rotate and as a result, the interaction of the Valence band and conduction band may have shifted resulting to increased band gap [6,14,17]. From Table 1, it was concluded that the band gap of the CH3NH3PbI3 hybrid perovskite film was modified significantly by the presence of silver nanoparticles resulting into a decreased band gap from 1.921-1.832 eV [9,27,32].…”
Section: Optical Band Gap G Ementioning
confidence: 95%
“…This was attributed to the crystal defects. It was assumed that the rotation of the PI3 octet may have been restricted to rotate and as a result, the interaction of the Valence band and conduction band may have shifted resulting to increased band gap [6,14,17]. From Table 1, it was concluded that the band gap of the CH3NH3PbI3 hybrid perovskite film was modified significantly by the presence of silver nanoparticles resulting into a decreased band gap from 1.921-1.832 eV [9,27,32].…”
Section: Optical Band Gap G Ementioning
confidence: 95%
“…However, it has been demonstrated that the electric field contribution in organic solar cells arises mainly at a high level of irradiation (1 sun) as a consequence of a charge accumulation in the device [56], and we suppose it to be negligible in our experimental conditions. In perovskite solar cells, a recent article [57] demonstrated the field free condition of the methyl-ammonium lead iodide (MAPI) layer under short and open circuit conditions; moreover, as already assumed in several works [58][59][60], we believe that a diffusion-based transport model could be a starting point for an investigation with the SATEM analysis. Further research is required in this direction to unravel the limiting mechanisms of the IPCE and optical-based analysis for the extraction of the charge collection capabilities of hybrid-organic solar cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigating the solar cells by simulation is a useful and a valuable tool to understand the device physics and optimize the efficiency. Modeling organic materials is considered challenging because the binding energy of the exciton should be taken into consideration for charge separation [11,12]. However, the exciton in perovskite materials exhibits a similar behavior as inorganic materials which make it possible to simulate the perovskite as an inorganic material using the available simulation tools [11,13].…”
Section: Introductionmentioning
confidence: 99%